POTENSI PURANA SEBAGAI MEDIA PENDIDIKAN GENERASI MUDA HINDU DI ERA SOCIETY 5.0 - I Dewa Gede Darma Permana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Abstract The young generation is the generation that will carry the burden and ideals of the nation in the future. This challenge is becoming more and more difficult as the world is now facing the era of Society 5.0, where people are becoming the center of innovation to open up new opportunities in terms of prosperity. For this reason, the younger generation of Hindus must always be ready to develop productive ideas while still being grounded in the teachings of Hinduism. A part of the Vedic Smerti scriptures namely Purana, is considered as a suitable medium of education for the younger generation of Hindus to have Suputra character and also to be productive. Keeping this in mind, this research is interested in exploring more deeply the potential of Purana stories that can be used as educational media for the younger generation of Hindus. This research also formulates several problems, namely related to the role of the Hindu young generation in the era of Society 5.0, the nature of Purana, and the use of Purana as a means of empowering the Hindu young generation. By using research methods with qualitative research types and literature studies and using data analysis of Miles and Huberman. The findings of this study indicate that the use of Purana has great potential as an educational medium in the form of visual arts, fine arts, books, comics and also miniature toys. Keywords: Puranas, Hindu Youth, Society 5.0